EFEKTIVITAS PELATIHAN KERJA TERHADAP PRESTASI KERJA KARYAWAN - Prita, Laras; Tarjono, Tarjono; Rianto, Toha (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2023)
This research was conducted at PT Indonesia Power Pelabuhanratu Sukabumi. The purpose of this study was to find out how the work performance of PT Indonesia Power Pelabuhanratu Sukabumi employees in relation to job training. The study population was 50 employees of PT Indonesia Power Pelabuhanratu Sukabumi. The sample used in this study is the census method, which is both primary and secondary data. Linear regression is the data analysis approach used. The results showed that job training positively influences employee job performance. Job training has an influence of 73.4% on employee job performance, while other factors have an influence of 26.6%. It was concluded that job training at PT Indonesia Power Pelabuhanratu Sukabumi has been good in influencing employee work performance.